Perancangan Antena MIMO Metamaterial Sub-6 GHz untuk Komunikasi Darurat Pascabencana Berbasis UAV - Tengku Machdalie Sofie; Gunawan Sihombing (Fuse-teknik Elektro, 2026)
Sub-6 GHz metamaterial MIMO antenna for post-disaster emergency communication applications based on Unmanned Aerial Vehicle (UAV). Damage to telecommunications infrastructure during disasters causes communication interruptions, so a fast, flexible, and reliable emergency communication system is needed. UAV technology was chosen because it has high mobility and is able to function as an air base station in disaster-affected areas. However, the implementation of the MIMO system on UAVs faces obstacles in the form of mutual coupling between antenna elements due to limited installation space. Therefore, this study integrates a Complementary Split Ring Resonator (CSRR) metamaterial structure on a MIMO microstrip antenna to improve antenna performance. The research method is carried out through the design, simulation, optimization, fabrication, and antenna testing stages using CST Studio Suite and ANSYS HFSS software. The antenna is designed at a working frequency of 3.5 GHz to 5.8 GHz using a Rogers RT5880 substrate with a 2x2 MIMO configuration. The parameters analyzed include return loss, VSWR, gain, bandwidth, mutual coupling, isolation, Envelope Correlation Coefficient (ECC), and radiation efficiency. The results showed that the antenna was able to work optimally at Sub-6 GHz frequencies with a return loss value reaching -31.2 dB, VSWR 1.08, a gain of 9.8 dBi, a bandwidth of 1.15 GHz, and a radiation efficiency of 87.4%. The use of CSRR metamaterials succeeded in reducing mutual coupling from -12 dB to -24 dB and increasing isolation to 24.1 dB. The low ECC value of 0.011 indicates excellent MIMO diversity performance. The implementation of the antenna on the UAV also showed stable communication, low latency, and good data transmission under moving conditions. Based on these results, CSRR-based metamaterial MIMO antennas have great potential to be applied to post-disaster emergency communication systems because they are able to improve communication quality, expand signal coverage, and support real-time communication efficiently